ANALISIS STRATEGI BERSAING BISNIS HOME INDUSTRY [ANALYSIS OF HOME INDUSTRY BUSINESS COMPETITIVE STRATEGY] - Maria Rijanto (Universitas Pelita Harapan, 2021)
The Food Industry is one of industry currently surviving and promising in Indonesia. In 2019 the food and beverage industry in Indonesia increased by 6.77%, and contributed to the national GDP of 7.35% so that this industrial sector can be relied upon. The home industry is one of the business segments that does not require large capital and can absorb a lot of labors. In the city of Bekasi, the market snack industry is one of the industries that is in great demand so that it is growing. This research was conducted in one of the home industries in Harapan Indah, Bekasi. In Harapan Indah, traditional snack industry has tight market competition. Mayona is home industry of traditional snack that has been established since 2002, currently Mayona has the goal of maximizing revenue in order to remain competitive in the current market industry. This research is using qualitative method. the respondents in this study were selected using purposive sampling. Respondent of this research are Mayona owner, Mayona employees, Mayona reseller,owner of retail traditional snack, consumer of enduser Mayona, and consumers of retail traditional snack. This study aims to 1) find out the strengths and weaknesses that Mayona currently has using SWOT analysis, 2) find out what are the external challenges and opportunities of Mayona by using SWOT analysis and Porter's Five Force analysis in the Mayona environment, 3) Propose appropriate strategies to Mayonna is differentiation by creating a competitive advantage.Abstrak dalam Bahasa Indonesia. Salah satu industri yang saat ini dapat bertahan dan menjanjikan adalah industri makanan. Di tahun 2019 industri makanan dan minuman di Indonesia mengalami kenaikan 6,77%, dan memberi kontribusi terhadap PDB nasional sebesar 7,35% sehingga sector industry ini dapat diandalkan. Home industry merupakan salah satu segmen usaha yang tidak membutuhkan modal besar dan dapat menyerap banyak tenaga kerja. Di kota Bekasi industri jajanan pasar termasuk industri yang banyak diminati sehingga mengalami pertumbuhan. Penelitian ini dilakukan pada salah satu home industry yang ada di Perumahan Harapan Indah kota Bekasi. Di perumahan Harapan Indah industri jajanan pasar memiliki persaingan yang ketat. Mayona merupakan salah satu home industry jajanan pasar yang sudah berdiri sejak tahun 2002, saat ini Mayona memiliki tujuan yaitu memaksimalkan pendapatan agar dapat tetap bersaing didalam industri jajanan pasar saat ini. Penelitian ini merupakan penelitian kualitatif, responden dalam penelitian ini dipilih dengan menggunakan purposive sampling. Responden dalam penelitian ini terdiri dari pemilik Mayona, karyawan Mayona, resellser Mayona, pemilik tempat titip jual, konsumen enduser Mayona, dan konsumen di tempat titip jual. Penelitian ini bertujuan untuk 1) mengetahui keunggulan dan kelemahan yang dimiliki Mayona saat ini dengan menggunakan analisis SWOT, 2) mengetahui yang menjadi tantangan dan kesempatan Mayona dengan menggunakan analisis SWOT dan analisis Porter’s Five Force pada lingkungan eksternal Mayona, 3) Usulan strategi yang tepat untuk Mayona adalah diferensiasi dengan menciptakan keunggulan kompetitif.